Tadpole of the Critically Endangered Sterling’s Toothed Toad (Oreolalax sterlingae) - Rowley, Jodi J. L.; Tapley, Benjamin; Chung, Nguyen Thanh; Altig, Ronald (Zootaxa, 2017)
Sterling’s Toothed Toad, Oreolalax sterlingae (Nguyen et al. 2013), was described from near the summit of the highest peak in Vietnam, Mount Fansipan, Lao Cai Province. The species is the only member of the genus in Vietnam and is presently known from a single stream system on Mount Fansipan at about 2800 m elevation. The closest congener occurs more than 200 km away in China (Fei et al. 2010), and the relationship of O. sterlingae within the genus is not known. Because of its extremely small range and profound habitat modifications and pollution at the site, O. sterlingae was recently assessed as Critically Endangered (IUCN SSC 2015).